Retrospective study on the microbial drug resistance profile and predictive risk factors in early infection of open fractures - Meng, Tai Ken; Sulong, Ahmad Fadzli; Mohd Yusof, Nazri (Kuliyyah of Medicine, IIUM, 2019)
Introduction: This study was conducted to evaluate the susceptibility of microorganisms involved in early infection of open fractures in orthopaedics to current prophylactic antibiotics practice and determine the association of various parameters related to the causative organism, patient, injury and management to the resistance of such microorganisms. Methods: This is a retrospective study that reviewed cases collected from the surgical operations record from January 2015 to December 2017 in Hospital Tengku Ampuan Afzan, Kuantan. A total of 179 cases were collected with 110 cases fulfilling the proposed inclusion / exclusion criteria. They all underwent routine debridement followed by culture and sensitivity. Previous clinical records were traced to identify the various risk factors for infection and evaluate these against the resistance of the microorganisms to prophylactic antimicrobial drugs. Results: Admission to the intensive care unit, blood transfusion, antibiotic regime and duration, fracture grade, injury severity score and duration of admission were all significantly associated with resistance of microorganism. The study also demonstrated the predominance of Gram-negative microorganisms constituting 65.9% of isolates. Gramnegative microorganisms were seen more in higher fracture grades and Injury Severity Scale, and longer duration of admission and antibiotic treatment. The overall susceptibility of microorganisms to antibiotics was also demonstrated with up to 68.6% resistance to cefuroxime and 36.9% to Gentamicin. Staphylococcus aureus and MRSA were the commonest Gram-positive organisms while Pseudomonas and Acinetobacter spp. the commonest Gram-negatives. Conclusion: Admission to Intensive Care Unit, blood transfusion, antibiotic regime and duration, fracture grade, injury severity score and duration of antibiotics have a significant positive predictive value to the development of resistance of microorganisms. The shift to predominantly Gram-negative microorganisms indicate an urgency to modify management of open fracture to achieve optimal results. This will also prevent the emergence of new multi-drug resistance microorganism which is already a worldwide public health problem.